Addressable and Color‐Tunable Piezophotonic Light‐Emitting Stripes. Issue 19 (15th March 2017) - Chen, Yan; Zhang, Yang; Karnaushenko, Daniil; Chen, Li; Hao, Jianhua; Ding, Fei; Schmidt, Oliver G.
Abstract : Piezophotonic light‐emitting devices have great potential for future microelectromechanical systems (MEMS) and nanoelectromechanical systems (NEMS) due to the added functionality provided by the electromechanical transduction coupled with the ability of light emission. Piezophotonic light‐emitting source based on Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (PMN–PT) bulk is severely restricted by many challenges, such as high voltage burden, low integration density, and micromanufacturing complexity. Developing chip‐integrated devices or incorporating such photonic components onto a Si platform is highly sought after in this field. In this work, the authors overcome the abovementioned problems by introducing single‐crystal PMN–PT thin films on Si as central active elements. Taking advantage of mature microfabrication techniques, arrays of PMN–PT actuators with small footprints and low operation voltages have been implemented. Each actuator can be individually addressed, generating local deformation to trigger piezophotonic luminescence from ZnS:Mn thin films. Moreover, the authors have realized continuous and reversible color manipulation of piezophotonic luminescence on a bilayer film of ZnS:Cu, Al/ZnS:Mn. The color tunability promises an extra degree of freedom and distinctly suggests its great potential in developing a more compact and colorful piezophotonic light sources and displays related applications together with the "single pixel" addressability. Abstract : An independently controlled, color‐tunable piezophotonic light‐emitting device is constructed which allows addressable tuning of emission color and intensity. The proof‐of‐concept device solves the main problems hampering the applications of piezophotonic luminescence devices, such as high voltage burden, not addressable, and low integration density, etc. This novel device offers a prospective way to develop Si‐integrated addressable and color‐tunable piezophotonic light‐emitting components.